(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The results of studies of the pozzolanic properties of zeolite tuffs from the Lerantsk mine in the Shirak region of RA have been presented. The laboratory tests have been shown that the addition of 5–20% zeolitic tuff to the cement clinker increases the strength of the cement stone by 21–24% over 28 days, due to the pozzolanic properties of the zeolite. In the process of clinker hydration, zeolite converts calcium hydroxide into the calcium hydrosilicate, as a result, calcium hydroxide is prevented from leaching out of the cement stone by about 40% and provides increased strength of the cement stone. It has also been found that the addition of zeolite tuff to the clinker leads to an increase in the specific gravity of the cement and a reduction in the initial and final setting time.